Analysis of international capital mobility in ASEAN-5 countries: savings- investment Nexus - Yong, Sze Wei; Rosita Haji Suhaimi,; Kueh, Jerome Swee Hui (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper analyzes the degree of the international capital mobility via the national savings and investment relationship in ASEAN-5 countries, namely Indonesia, Malaysia, Thailand, the Philippines and Vietnam over the period 1980 to 2013 using panel data method. Besides, this paper also investigates the impact of the international capital mobility for three sub-periods: period prior to 1997 Asian financial crisis (1980-1996), period after the 1997 Asian financial crisis (1997-2007) and period after the 2008 global financial crisis (2008-2013). The findings of this paper indicate that the degree of the international capital mobility is at the moderate level for the period 1980 to 2013. However, the finding of the sub-periods after 1997 Asian financial crisis and 2008 global financial crisis indicating an upsurge degree of the capital mobility in ASEAN-5 countries. This might be due to the adoption of export oriented policy and the capital account liberalization in the 1990s and closer economic cooperation in the East Asia region aftermath both of the global and Asian financial crises. It is crucial for government and policy makers to monitor closely on the trend of international capital mobility to prevent financial risks as well as develop efficient policy and financial regulatory to achieve the policy coordination among the ASEAN members.